2018
DOI: 10.31584/jhsmr.2018.36.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Iron Deficiency Anemia in High School Girls in Nakhon Si Thammarat, Thailand

Abstract: Objective: To determine the prevalence and causes of anemia in high school girls in Nakhon Si Thammarat, Thailand. Material and Methods: This cross-sectional study was performed in high school girls aged 15-18 years old. Blood samples were collected for hematological parameters, iron profiles and blood smear examination. The recall 24-hour dietary data were collected using a questionnaire to determine and calculate daily iron intake. For purposes of the study, anemia was defined as hemoglobin (Hb) of <12 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…This comparison showed that MCV values in our study were just above that for vegetarians (79.8 fL vs. 78.4 fL), while MCH values were slightly lower (26.0 pg vs. 27.2) [ 45 ]. Furthermore, MCV and MCH values in Sundanese girls were similar to those for high school girls who suffer iron deficiency without anemia in Nakhon Si Thammarat, Thailand (MCV = 80.0 fL; MCH = 26.9 pg) [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This comparison showed that MCV values in our study were just above that for vegetarians (79.8 fL vs. 78.4 fL), while MCH values were slightly lower (26.0 pg vs. 27.2) [ 45 ]. Furthermore, MCV and MCH values in Sundanese girls were similar to those for high school girls who suffer iron deficiency without anemia in Nakhon Si Thammarat, Thailand (MCV = 80.0 fL; MCH = 26.9 pg) [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…Based on WHO guidelines stating that a prevalence of anemia between 20.0% and 39.9% is of moderate public health significance [ 28 ], anemia is indeed a public health problem among the Sundanese adolescent girls in the area. Among all anemic subjects, the proportion of subjects with IDA was 22.2%, which was considerably higher than in other developing countries such as Iran (13.9%) [ 29 ], Ethiopia (11%) [ 6 ], and Thailand (5.7%) [ 30 ]. However, the prevalence of IDA was lower compared to other Asian countries such as Malaysia (34%) [ 31 ] and Bangladesh (32%) [ 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…4 On the contrary, only 8.3% of anemia was present in high-school girls aged 15 to 18 years. 8 Furthermore, a study conducted on adolescent aged 15 to 17 years in northeastern Thailand, the prevalence of anemia was found 21.1% (8.1% in males and 13.0% in females) and 16.6% (8.9% in males and 7.7% in females) in Mukdahan and Roi-Et Province, respectively. 14 Based on the consideration of the age-group and gender, the proportion of anemia was higher in females than males.…”
Section: Discussionmentioning
confidence: 96%
“…7 Iron deficiency was also the main cause of anemia (13 of 19 cases) in girls in the high school. 8 Regarding to puberty, adolescents require an increased intake of nutrients for rapid growth and physiological development, particularly in women, as menstrual combination can be one of the reasons that lead to anemia. 9 Therefore, the objective of this study was to determine the prevalence and causes of anemia in Muslim secondary school students in Thasala District, Nakhon Si Thammarat Province in southern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian yang Siva et al (2016), Sarakul et al (2018), dan Ahankari et al (2017) mendapatkan hasil remaja putri yang menderita yaitu mengalami menarche, konsumsi zat besi <15 mg/hari, tidak konsumsi sayuran, dan tidak konsumsi suplemen zat besi. Sesuai dengan hasil penelitian K. & D. tahun 2017 menyatakan bahwa hanya sedikit remaja putri yang konsumsi kacang-kacangan, sehingga didapatkan angka kejadian anemia.…”
Section: Tingkat Asupan Zat Besi Dan Pola Menstruasiunclassified